Afghan Peace Talks A Primer - Shinn, James (RAND Corporation, 2011)
The objective of a negotiated peace in Afghanistan has been firmly embraced by most of the potential parties to a treaty. However, arriving at an agreement about the sequencing, timing, and prioritization of peace terms is likely to be difficult, given the divergence in the parties' interests and objectives. The U.S. objective in these negotiations should be a stable and peaceful Afghanistan that neither hosts nor collaborates with terrorists.